Zirconium metal‐organic framework supported highly‐dispersed nanosized BiVO4 for enhanced visible‐light photocatalytic applications. Issue 11 (17th February 2016) - Cheng, Cong; Fang, Jianzhang; Lu, Shaoyou; Cen, Chaoping; Chen, Yi; Ren, Lu; Feng, Weihua; Fang, Zhanqiang
Abstract: BACKGROUND: As a super stable zirconium based metal‐organic framework, Zr6 (OH)4 (C8 H6 O4 )6 (UiO‐66) is considered a competitive candidate to conjugate with photocatalyst to enhance photocatalytic activity. In this study, highly dispersed bismuth vanadate (BiVO4 ) nanoparticles grown in situ upon the surfaces of UiO‐66 were synthesized through a simple method, and the photocatalytic activities were investigated by measuring the degradation of rhodamine B (RhB) under visible light irradiation. RESULTS: The results show that UiO‐66@BiVO4 composite with Bi:Zr molar ratio of (1:1) was the optimum hybrid and exhibited much higher photocatalytic activities than that of pure BiVO4 . Furthermore, the photocatalyitc mechanism of RhB degradation by UiO‐66@BiVO4 was also investigated, the photodegradation of RhB was mainly caused by the super oxide ions (· O2 − ). The lone pair electrons of surface group –OH and –COOH of UiO‐66 attract the photogenerated holes (h + ), which effectively prevent the recombination of electrons and holes. CONCLUSIONS: The enhanced separation of photogenerated electron–hole pairs through interfaces between BiVO4 and UiO‐66 led to improvement of the photocatalytic activity. The study showed a degradation mechanism for RhB wasterwater treatment. © 2016 Society of Chemical Industry